Vygotsky's Sociocultural Theory Constructivism in Art Education - Kadek Hariana (Education Journal, 2021)
Sociocultural theory grew out of the work of seminal psychologist Lev Vygotsky, who believed that parents, caregivers, peers and culture in general were responsible for developing higher-order functions. According to Vygotsky, learning has a basis in interacting with other people. Once this has happened, the information is then integrated at the individual level. This concept is in accordance with the cooperative learning model in Art Education which requires a process of social interaction between students and students and between students and educators, in the process of finding problem-solving concepts in creating or creating works. Vygotsky's theory of cognitive development focuses on three important factors, namely Culture, Language, and the Zone of Proximal Development. Vygotsky's theory focuses on scaffolding, which is providing full assistance to children at the initial stage of their learning and then reducing them to further provide opportunities for children to carry out their responsibilities so that they can finally solve their own problems. This concept can be maximally applied in the process of learning art for children so that children can improve their cognitive realm and their level of creativity can develop.